Pulmonary arteriovenous malformation and inherent complications with solitary lung nodule biopsy—literature overview and case report - Cung-Van Cong, MD, PhD; Dinh-Van Luong, MD, PhD; Tran-Thi Tuan Anh, MD; Nguyen-Le Nhat Minh, MD; Tran-Thi Ly, PhD; Nguyen Minh Duc, MD (Radiology Case Reports, 2022)
Pulmonary arteriovenous malformation, also known as an arteriovenous fistula, is typically a congenital disease caused by structural deficiencies, particularly the lack of capillary wall development, leading to the abnormal dilation of the pulmonary capillaries. The majority of pulmonary arteriovenous malformation cases are associated with Rendu–Osler–Weber syndrome, also known as hereditary hemorrhagic telangiectasia. Pulmonary arteriovenous malformation rarely occurs due to chest trauma. Pulmonary arteriovenous malformations are long-lasting and often first diagnosed in adults. More than two-thirds of pulmonary arteriovenous malformation lesions are found in the lower lung lobe and the subpleural area, and the vast majority of cases present with the monofocal form. The initial diagnosis is often based on the identification of a solitary pulmonary nodule. However, a solitary nodule detected on chest computed tomography that is not correctly diagnosed as pulmonary arteriovenous malformation, even after intravenous contrast injection, can lead to the performance of a transthoracic biopsy. Biopsy of pulmonary arteriovenous malformations can lead to stroke occurrence, during which the patient often presents with severe pleural bleeding, which can have lifelong consequences if not immediately treated. We report a case of pulmonary arteriovenous malformation that was discovered incidentally in an adult patient who underwent non-contrast computed tomography. Misdiagnosis occurred, and transthoracic lung biopsy was performed. Complications were discovered late, and the patient underwent surgical pulmonary arteriovenous malformation removal and was treated for hemothorax.